Cementitious compositions, cement-based structures, and methods of forming the same
Patent Information
- Application Number
- CN202611145720.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2017-09-18
- Filing Date
- 2018-09-18
- Publication Date
- 2026-10-30
AI Technical Summary
因此,基于SHCC的结构的生产会消耗大量的能量,并且会导致大量的二氧化碳(CO2)
Smart Images

Figure CN123003237A_ABST
Abstract
Description
[0001] Divisional application statement
[0002] This application is a divisional application of Chinese patent application No. 2018800746757, filed on September 18, 2018, entitled "Cement-based composition, cement-based structure, and method of forming the same".
[0003] Cross-reference to related applications
[0004] This application claims priority to Singapore Patent Application No. 10201707698R, filed on September 18, 2017, the contents of which are incorporated herein by reference in their entirety for all purposes. Technical Field
[0005] Various aspects of this disclosure may relate to a cementitious composition. Various aspects of this disclosure may relate to a cement-based structure. Various embodiments may relate to methods of forming a cementitious composition and / or a cement-based structure. Background Technology
[0006] Strain-hardening cementitious composites (SHCCs) represent a group of building materials with excellent mechanical properties and environmental durability. SHCCs typically achieve a tensile strain capacity of at least 1%, which is approximately 100 times that of conventional concrete. This exceptional tensile performance is achieved by adding a small fraction of fibers, which facilitates the formation of multiple microcracks with a close crack width, rather than the few large cracks seen in conventional concrete. The excellent tensile ductility and close crack width result in greater corrosion resistance and enhance the potential for self-healing cracks in SHCC-based structures. Although a wide variety of fibers, such as metal fibers, polymer fibers, and natural fibers, have been used to manufacture SHCCs, the choice of materials for the matrix composition remains relatively limited.
[0007] SHCC typically requires a high Portland cement (PC) content. Therefore, the production of SHCC-based structures consumes a significant amount of energy and results in substantial amounts of carbon dioxide (CO2). Summary of the Invention
[0008] Various embodiments may provide a cementitious composition. The cementitious composition may include a mixture comprising a binder component, including reactive magnesium oxide cement (RMC). The mixture may further include water. The cementitious composition may also include one or more fibers dispersed in the mixture.
[0009] Various embodiments may provide a cement-based structure. The cement-based structure may include a matrix comprising one or more hydrated magnesium carbonates. The cement-based structure may include one or more fibers embedded in the matrix.
[0010] Various embodiments may provide a method for forming a cementitious composition. This method may include forming a mixture. The mixture may include a binder component comprising activated magnesium oxide cement. The mixture may also include water. The method may include dispersing one or more fibers in the mixture.
[0011] Various embodiments may provide a method for forming a cement-based structure. This method may include forming a matrix comprising one or more hydrated magnesium carbonates. One or more fibers may be embedded in the matrix. Attached Figure Description
[0012] The invention will be better understood with reference to the detailed description when considered in conjunction with non-limiting examples and the accompanying drawings, wherein:
[0013] Figure 1 A general description of the cementitious compositions according to various embodiments is shown;
[0014] Figure 2 A general description of the cement-based structure according to various embodiments is shown;
[0015] Figure 3 This is a schematic diagram illustrating a method for forming a cementitious composition according to various embodiments;
[0016] Figure 4 This is a schematic diagram illustrating a method for forming a cement-based structure according to various embodiments;
[0017] Figure 5A It is a graph showing the change of weight percentage (in percentage or %) / heat flow (in milliwatts or mW) with temperature (in degrees Celsius or °C). The graph shows the results of thermogravimetric analysis (TGA) and differential thermal analysis (DGA) of the samples formed from mixture 1 and mixture 2 according to various embodiments.
[0018] Figure 5B It is a plot of tensile stress (expressed in megapascals or MPa) versus tensile strain (expressed as a percentage or %), which shows the uniaxial tensile stress-strain curve of the sample formed from mixture 1 according to various embodiments.
[0019] Figure 5C It is a plot of tensile stress (expressed in megapascals or MPa) versus tensile strain (expressed as a percentage or %), which shows the uniaxial tensile stress-strain curves of the sample formed from mixture 2 according to various embodiments.
[0020] Figure 6 This is a plot of the fiber bridging stress (σ) as a function of crack opening displacement (δ). The plot shows the tensile stress-crack opening displacement curve and strain hardening criterion, illustrating the constitutive law of fiber bridging.
[0021] Figure 7 It is a graph showing the cumulative fraction (expressed as a percentage or %) as a function of particle diameter (expressed in micrometers or μm), which illustrates the particle size distribution of active magnesium oxide cement (RMC) and fly ash (FA) used in the compositions according to various embodiments.
[0022] Figure 8A A rheometer for measuring samples according to various embodiments is shown;
[0023] Figure 8B Test setups for measuring samples according to various embodiments are shown;
[0024] Figure 9A A top view and a side view of a dog bone-shaped mold according to various embodiments are shown;
[0025] Figure 9B Test setups for performing uniaxial tensile tests on samples according to various embodiments are shown.
[0026] Figure 10A This is a plot of torque τ (in Pascals or Pa) as a function of shear rate N (per second or 1 / s), showing the torque shear rate (τ-N) of sample FA60-0.53 according to various embodiments at 6 minutes, 12 minutes, and 18 minutes.
[0027] Figure 10B This is a plot of torque τ (in Pascals or Pa) as a function of shear rate N (per second or 1 / s), showing the torque shear rate (τ-N) of sample FA60-0.53 according to various embodiments at 6 minutes, 12 minutes, and 18 minutes.
[0028] Figure 11A A plot showing the plastic viscosity (in Pascals seconds or Pas) as a function of fly ash / binder ratio (FA / b) (in percentage or %) is presented, illustrating the effect of water and fly ash content on the plastic viscosity of the mixture according to various embodiments;
[0029] Figure 11B A plot showing the yield stress (in Pascals or Pa) as a function of fly ash / binder ratio (FA / b) (in percentage or %) is shown, illustrating the effect of water and fly ash content on the yield stress of the mixture according to various embodiments;
[0030] Figure 12A It is a plot of tensile stress (expressed in megapascals or MPa) versus tensile strain (expressed as a percentage or %), illustrating the tensile stress-strain curves of sample NC-12-0.41 after 7 days of curing according to various embodiments;
[0031] Figure 12B It is a plot of tensile stress (expressed in megapascals or MPa) versus tensile strain (expressed as a percentage or %), illustrating the tensile stress-strain curves of sample NC-12-0.41 after curing for 28 days according to various embodiments.
[0032] Figure 12C It is a plot of tensile stress (expressed in megapascals or MPa) versus tensile strain (expressed as a percentage or %), illustrating the tensile stress-strain curves of sample OC-12-0.41 after 7 days of curing according to various embodiments;
[0033] Figure 12D It is a plot of tensile stress (expressed in megapascals or MPa) versus tensile strain (expressed as a percentage or %), illustrating the tensile stress-strain curves of sample OC-12-0.53 after 7 days of curing according to various embodiments.
[0034] Figure 12E It is a plot of tensile stress (expressed in megapascals or MPa) versus tensile strain (expressed as a percentage or %), illustrating the tensile stress-strain curves of sample OC-8-0.53 after 7 days of curing according to various embodiments;
[0035] Figure 13 The image shows a typical crack distribution in a destructive specimen (NC-12-0.41 cured for 7 days) after unloading according to various embodiments;
[0036] Figure 14A It illustrates various embodiments. Figure 13 An image of the fracture surface of the specimen shown;
[0037] Figure 14B It is based on the various implementation methods Figure 14AThe image shown is a field emission scanning electron microscopy (FESEM) image of the pulled-out fiber.
[0038] Figure 14C It is based on the various implementation methods. Figure 14B Field emission scanning electron microscopy (FESEM) image of residual tunnels in the matrix after the fibers have been pulled out;
[0039] Figure 15 It is a plot of mass (expressed as a percentage or %) / heat flow (expressed as milliwatts or mW) as a function of temperature (expressed as degrees Celsius or °C), which shows the thermogravimetric analysis (TGA) curves and differential scanning calorimetry (DSC) curves of sample OC-12-0.53 according to various embodiments. Detailed Implementation
[0040] The following detailed description refers to the accompanying drawings, which illustrate specific details and embodiments through which the invention can be practiced by way of example. These embodiments are described in sufficient detail to enable those skilled in the art to practice the invention. Other embodiments can be utilized, and structural and logical changes can be made, without departing from the scope of the invention. The various embodiments are not necessarily mutually exclusive, as some embodiments can be combined with one or more other embodiments to form new embodiments.
[0041] Embodiments described in the context of a method, composition, or structure are similarly effective for other methods, compositions, or structures. Similarly, embodiments described in the context of a method are similarly effective for compositions and / or structures, and vice versa.
[0042] Features described in the context of one implementation may be adapted accordingly to the same or similar features in other implementations. Features described in the context of one implementation may be adapted accordingly to other implementations, even if not explicitly described in those other implementations. Furthermore, additions and / or combinations and / or substitutions described for features in the context of one implementation may be adapted accordingly to the same or similar features in other implementations.
[0043] The term "above" as used in relation to deposited material formed "above" a side or surface can be used herein to mean that the deposited material can be formed "directly" on the implied side or surface, for example, in direct contact with the implied side or surface. The term "above" as used in relation to deposited material formed "above" a side or surface can also be used herein to mean that the deposited material can be formed "indirectly" on the implied side or surface, which has one or more additional layers disposed between the implied side or surface and the deposited material. That is, "above" a first layer and a second layer can mean that the first layer is directly on the second layer, or that the first and second layers are separated by one or more intermediate layers.
[0044] In the context of the various implementations, the articles “a,” “an,” and “the” used with respect to a feature or element include references to one or more features or elements.
[0045] In the context of the various implementations, the term “about” or “approximately” applied to numerical values covers both precise values and reasonable variances.
[0046] As used herein, the term “and / or” includes any and all combinations of one or more of the related listed items.
[0047] Activated magnesium oxide (MgO) cement, or RMC, is an alternative binder. Unlike hydraulic Portland cement, where hardening is a result of cement hydration, activated MgO cement (RMC) hardens through the carbonization of brucite (Mg(OH)2) with carbon dioxide (CO2). In practice, activated MgO cement (RMC) is first mixed with water and reacted to form brucite. The brucite is then carbonized using ambient CO2 in the air or elevated CO2 conditions in a controlled environment, causing it to solidify into a hardened matrix comprising various hydrated magnesium carbonates (HMC). Hydrated magnesium carbonate can have the formula xMg(CO)3·yMg(OH)2·zH2O. The hardened, dense carbonate network reduces sample porosity and can provide bonding strength in RMC-based samples.
[0048] In addition to laboratory-scale samples reported in numerous studies, earlier research has demonstrated the use of RMC in the production of commercial-scale masonry units, highlighting its feasibility for use in a variety of non-structural applications. Recent research using RMC as a binder focuses on understanding the factors influencing the carbonation and related strength development of RMC formulations, including mixing design, curing conditions, and the use of additives, resulting in concrete strengths up to ~60 MPa at 28 days.
[0049] The advantages of activated MgO cement over Portland cement are twofold. First, the calcination temperature of the minerals used to manufacture activated MgO cement (approximately 750°C) is likely much lower than that of Portland cement (approximately 1450°C), allowing the use of alternative fuels. Second, the setting and hardening of brucite can utilize carbonization to sequester CO2 from the atmosphere. This makes activated MgO cement a potential green cement to replace traditional Portland cement. Activated MgO cement has already been used to partially or completely replace Portland cement in the preparation of building materials such as masonry blocks.
[0050] In the preparation of strain-hardening cement-based composites (SHCCs), reactive MgO cement may be a good and sustainable alternative to Portland cement.
[0051] On the other hand, the active MgO-based matrix is brittle and cannot be reinforced with traditional steel bars due to the high risk of steel corrosion. The relatively low pH (i.e., ~10) of the carbonized RMC formulation may pose a challenge in steel reinforcement applications, as the loss of passivated surfaces at this relatively low alkalinity exposes them to corrosion, potentially leading to structural safety issues. The carbonization of the MgO binder lowers the pH of the matrix, resulting in depassivation and subsequent corrosion of the steel reinforcement.
[0052] Due to its superior mechanical properties, such as high tensile ductility, high damage tolerance, and fine crack width, the resulting strain-hardening reactive MgO composite (SHMC) can be used in many unreinforced applications, such as the retrofitting of unreinforced masonry walls, road overlay, and surface repair of dams and retaining walls. Other potential applications of unreinforced SHMC may include shotcrete for the lining of underground rock caverns and tunnels.
[0053] Despite significant improvements in mechanical properties resulting from ongoing research into RMC formulations, RMC-based concrete is still considered a brittle material, which could greatly benefit from its use in strengthening structural components.
[0054] Therefore, there may be a great need to enhance the toughness of this material, which could greatly broaden the potential applications of active MgO cement.
[0055] Alternative methods to enhance the ductility of RMC-based formulations may need to be developed to expand the application of RMC in the construction industry. The inclusion of small amounts of short polymer fibers has proven highly effective in eliminating the brittleness of Portland cement (PC)-based composites and enhancing their tensile ductility.
[0056] As highlighted above, one of the successful derivatives involving the use of fibers is engineered cementitious composite (ECC), which includes polymer fibers. The fibers may constitute a portion of the volume, typically about 2%. Unlike strain-softening conventional PC, ECC exhibits strain-hardening behavior because the tensile stress in ECC continues to increase even in the presence of cracks. ECC samples can achieve tensile ductility of about 1% to about 5% by forming multiple fine cracks (<100 μm) at very small intervals (about 1 mm to about 5 mm). The tensile properties of ECC can be further tuned using micromechanics to achieve a variety of properties, such as high impact resistance and fatigue resistance. Therefore, to increase the use of RMC without relying on steel reinforcement, it may be desirable to achieve similar tensile strain-hardening behavior and high ductility in RMC-based formulations by adding short fibers (e.g., polymer fibers).
[0057] Despite the rapid development of SHCC and reactive MgO cement, both technologies possessing excellent mechanical / durability properties and good sustainability, respectively, they have never been integrated. Various embodiments may involve a CO2-sequestered strain-hardening brittle matrix structure or composite material formed using reactive MgO cement as a binder.
[0058] Various embodiments may relate to a cementitious composition. Various embodiments may relate to a cement-based structure. A cement-based structure may refer to a cement-based composite material. In various embodiments, the term "cement-based structure" may be used to refer to the microstructure of the composite material, i.e., the internal structure of the composite material. Cementitious compositions may be used to form cement-based structures or composite materials. That is, the phrase "cementitious composition" may refer to a mixture of composite materials (before hardening).
[0059] Figure 1 A general description of a cementitious composition 100 according to various embodiments is shown. The cementitious composition 100 may include a mixture 102, which includes a binder component 104 comprising activated magnesium oxide cement (RMC). The mixture may further include water 106. The cementitious composition 100 may also include one or more fibers 108 dispersed in the mixture 102.
[0060] That is, various embodiments may involve a cementitious composition 100, which includes a binder component 104 and water 106, and the binder component 104 and water 106 may form a mixture 102. The composition 100 may also include one or more fibers 108 incorporated into the mixture 102.
[0061] To avoid any doubts, Figure 1 This is only intended to illustrate the various possible components of composition 100 according to the various embodiments, and may not, for example, indicate the arrangement of different components in composition 100.
[0062] In various embodiments, composition 100 may be referred to as cement.
[0063] Activated magnesium oxide cement (RMC) can primarily consist of magnesium oxide (MgO). Activated magnesium oxide cement may include small amounts of other materials, such as calcium oxide (CaO), silicon dioxide (SiO2), iron oxide (Fe2O3), and / or aluminum oxide (Al2O3). Activated magnesium oxide cement may contain greater than about 50% by mass of magnesium oxide, for example, greater than about 80% by mass, greater than about 90% by mass, greater than about 95% by mass, greater than about 96% by mass, greater than about 97% by mass, greater than about 98% by mass, greater than about 99% by mass, or about 100% by mass of magnesium oxide.
[0064] SHCC is an excellent building material, but due to the high amount of Portland cement used, it may not be environmentally friendly. Activated MgO cement (RMC) offers sustainability advantages due to its lower manufacturing temperature and ability to sequester carbon dioxide. Various implementations can integrate activated MgO cement into SHCC, resulting in sustainable building materials. Compared to conventional Portland cement-based SHCC, these implementations can reduce carbon dioxide emissions from raw material manufacturing to on-site SHCC application by at least approximately 40% to approximately 60%.
[0065] In various embodiments, the binder component 104 may further comprise any one or more binders selected from hydraulic cement, fly ash, silica fume, and finely ground blast furnace slag. The addition of such a binder can significantly reduce production costs and contribute to mechanical properties through the reaction of cementitious materials and pozzolanic materials. This binder can be obtained from industrial waste.
[0066] In various embodiments, binder component 104 may include activated magnesium oxide cement (RMC) and fly ash (which may alternatively be referred to as fly ash (FA)). Due to the spherical shape of FA, it can increase flowability and improve the rheological properties of the composition, which reduces interparticle friction. In various embodiments, fly ash may be any value comprising about 0% to about 60% by mass, for example, about 0% to about 30% by mass of binder component 104. Fly ash may primarily comprise silica (SiO2) and alumina (Al2O3). Silica (SiO2) and alumina (Al2O3) may comprise more than 50% by weight, for example, more than 60% by weight, more than 70% by weight, more than 80% by weight of fly ash. Fly ash may also include small amounts of other materials, such as magnesium oxide (MgO), calcium oxide (CaO), iron oxide (Fe2O3), potassium oxide (K2O), titanium oxide (TiO2), etc.
[0067] In various other embodiments, the binder component 104 may consist of only active magnesium oxide cement.
[0068] In various embodiments, the mass percentage of the active magnesium oxide cement in the binder component 104 can be any percentage value selected from about 40% to about 100%.
[0069] In various embodiments, the mass ratio of water to binder components (w / b ratio) can be any ratio selected from about 0.4 (i.e., 0.4:1) to about 0.8 (i.e., 0.8:1), for example, from about 0.4 (i.e., 0.4:1) to about 0.6 (i.e., 0.6:1). A low w / b ratio may result in higher viscosity and better fiber dispersion. A low w / b ratio may also be associated with higher compressive strength of the resulting composite material. However, reducing the w / b ratio, for example from 0.53 to 0.41, may enhance the initial crack strength and ultimate tensile strength, and result in better ductility.
[0070] In various embodiments, mixture 102 may further include a water-reducing agent. The water-reducing agent may be a sodium hexametaphosphate (Na(PO3)6) solution. The mass percentage of the water-reducing agent relative to the binder component may be any percentage value selected from about 2% to about 4%.
[0071] In various embodiments, mixture 102 may further include a viscosity control agent. The viscosity control agent may be hydroxypropyl methylcellulose (HPMC). The mass percentage of the viscosity control agent relative to the binder component may be any percentage value selected from about 0.05% to about 0.5%.
[0072] Water 106 may be present in mixture 102, working in conjunction with water-reducing agents and / or viscosity control agents to achieve sufficient rheological properties.
[0073] In various embodiments, the mixture 102 in the fresh phase may be Bingham liquid.
[0074] One or more fibers 108 may be one or more types of fibers selected from metal fibers, polymer fibers and natural fibers.
[0075] One or more fibers 108 or polymer fibers may be any type of fiber selected from polyvinyl alcohol (PVA) fibers, ethylene acetate (EVOH) fibers, (PE) polyethylene fibers, acrylic fibers, polypropylene (PP) fibers and acrylamide fibers.
[0076] The volume percentage of one or more fibers 108 in the cementitious composition can be any percentage value selected from about 0.5% to about 10%, about 1% to about 3%, for example about 1% to about 2%.
[0077] One or more fibers 108 may have an average tensile strain capacity of about 1% to about 10%, for example, about 3% to about 7%. One or more fibers 108 may have an average diameter selected from about 10 μm to about 60 μm, for example, about 25 μm to about 50 μm, for example, about 35 μm to about 45 μm. One or more fibers 108 may have an average length selected from about 5 mm to about 30 mm, for example, about 6 mm to about 25 mm, for example, about 6 mm to about 18 mm, for example, about 8 mm to about 12 mm. As described in more detail below, an increase in fiber aspect ratio may result in improved tensile strength and / or ductility.
[0078] In various embodiments, each of the one or more fibers 108 may include an oil coating. The oil may be polyoxymethylene. Any other suitable oil may also be used.
[0079] In various embodiments, one or more fibers 108 may be hydrophilic fibers. When the composition 100 cures, the hydrophilicity of certain types of fibers 108 can introduce strong interfacial bonding between the fibers and the surrounding matrix. An oiling agent may be applied to prevent excessive enhancement of the interfacial bonding. The oiling agent can help improve tensile ductility.
[0080] In various other embodiments, each of the one or more fibers 108 may be excluded, that is, there may be no oil coating.
[0081] Various embodiments may involve using fiber 108 to reinforce a brittle matrix comprising reactive MgO cement. The resulting strain-hardening reactive MgO composite material (SHMC) or structure may have a strength of approximately 1,500 kg / m³. 3Approximately 2,500 kg / m 3 The density can be any value within the range, and it can have at least about 1% tensile ductility. Various embodiments can seal up to 1 tonne of carbon dioxide (CO2) during the curing process before reaching their designed compressive strength.
[0082] Various embodiments may involve composition 100 formed by any suitable method described herein.
[0083] Various embodiments may involve compositions comprising different proportions of activated MgO cement (RMC), water, and fiber. Additional optional components, such as water-reducing agents and viscosity control agents, may be required to adjust the thixotropic and viscosity properties to achieve sufficient processability and uniform fiber dispersion.
[0084] Active MgO cement can be obtained by calcining magnesium carbonate or magnesium hydroxide at temperatures below 1000°C. Other binders, such as hydraulic cement, fly ash, silica fume, and finely ground blast furnace slag, can be added as optional supplements. The addition of this binder derived from industrial waste can significantly reduce the cost of MgO and can contribute to mechanical properties through cementitious and pozzolanic reactions. The fraction of active MgO cement in the binder component can be any percentage selected from about 40% to about 100%. The binder can solidify in the presence of water and gains strength upon exposure to carbon dioxide.
[0085] Water can be present in the fresh mixture, working in conjunction with water-reducing agents and / or viscosity control agents or modifiers to achieve sufficient rheological properties. A water-to-binder ratio of any value selected from about 0.4 to about 0.8 can be used to obtain the desired strength. After determining the water content in the composite material, water-reducing agents can be used to adjust the desired level of processability. The required amount of water-reducing agent can vary depending on the water-to-binder ratio, the composition of the binder, and / or the type of water-reducing agent. An illustrative water-reducing agent may be a sodium hexametaphosphate (NaHMP; Na(PO3)6) solution. The amount of (Na(PO3)6) can be any percentage selected from about 2% by mass to about 4% by mass of the binder. An illustrative viscosity control agent is hydroxypropyl methylcellulose (HPMC). A typical amount of HPMC can be any percentage selected from about 0.05% by mass to about 0.5% by mass of the binder.
[0086] The fiber can be one or more of any suitable type of discontinuous fiber and can be provided in bundles. Examples of suitable fibers may include, but are not limited to: polyvinyl alcohol (PVA) fiber, ethylene vinyl acetate (EVOH) fiber, polyethylene (PE) fiber, acrylic fiber, polypropylene (PP) fiber, and acrylamide fiber.
[0087] The amount of fiber in the composition, the nature of the fiber, and / or the size of the fiber can vary. The desired amount of fiber may be such that it is high enough to provide the composition with the desired extensibility, but low enough to allow for self-compaction.
[0088] In various embodiments, the tensile strain capacity of the composition can be any percentage selected from about 1% to about 10%, for example about 3% to about 7%.
[0089] Generally, for traditional fiber sizes, if the fiber content exceeds 2.5%, it is difficult to achieve density without vibration.
[0090] The fibers included in SHMC can be selected from any percentage from about 0.5 vol% to 10 vol%, for example from about 1 vol% to about 3 vol%, for example from about 1 vol% to about 2 vol%. The diameter of the fibers can be from about 10 μm to about 60 μm, for example from about 10 μm to about 20 μm, or from about 25 μm to about 50 μm, for example from about 35 μm to about 45 μm, and the length can be from about 5 mm to about 30 mm, for example from about 6 mm to about 25 mm, for example from about 6 mm to about 18 mm, for example from about 8 mm to about 12 mm.
[0091] In various embodiments, the fiber may be PVA fiber. The surface of the PVA fiber may be coated with an oil (e.g., polyoxymethylene) up to about 1.5% of the fiber weight, for example, coating with any value selected from about 0.8% to about 1.2% by weight relative to the fiber. The fiber may be coated with the oil by any conventional method, such as by dip coating or spray coating. Other oils may also be used. The hydrophilicity of PVA fiber may introduce strong interfacial bonding between the fiber and the surrounding matrix. An oil may be applied to prevent excessive enhancement of interfacial bonding.
[0092] Various embodiments may relate to a cement-based structure. The cement-based structure may be a composite structure. The cement-based structure may be formed from a cementitious composition.
[0093] Figure 2 A general description of cement-based structures according to various embodiments is shown. Cement-based structure 200 may include a matrix 202 comprising one or more hydrated magnesium carbonates. Cement-based structure 200 may include one or more fibers 204 embedded in the matrix 202.
[0094] In other words, various embodiments may provide a structure having fibers 204 within a matrix 202, the matrix 202 comprising one or more hydrated magnesium carbonates.
[0095] Structure 200 can be a composite structure and may be referred to as a composite material. Structure 200 can be formed by hardening a cementitious composition. In various embodiments, structure 200 can be formed by curing a cementitious composition.
[0096] To avoid any doubts, Figure 2 This is only intended to illustrate the various possible components of the cement-based structure 200 according to the various embodiments, and may not, for example, represent the arrangement of different components within the structure 200.
[0097] In various embodiments, one or more hydrated magnesium carbonates may be selected from: magnesia (MgCO3·3H2O), hydromagnesite (4MgCO3·Mg(OH)2·4H2O), spheroidal magnesia (4MgCO3·Mg(OH)2·5H2O) and fibrous magnesite (MgCO3·Mg(OH)2·3H2O).
[0098] One or more fibers 204 can be bonded to the matrix 202. Interfacial bonding may exist between the matrix 202 and one or more fibers 204.
[0099] One or more fibers 204 may extend throughout the structure 200 or may be uniformly distributed.
[0100] In various embodiments, the cement-based structure 200 may be concrete. In various other embodiments, the cement-based structure 200 may be mortar.
[0101] Various implementations may involve a structure 200 formed by any suitable method described herein.
[0102] Various embodiments may relate to a method for forming a cementitious composition. Figure 3 This is a schematic diagram illustrating a method for forming a cementitious composition according to various embodiments. The method may include, in step 302, forming a mixture. The mixture may include a binder component comprising activated magnesium oxide cement. The mixture may also include water. The method may include, in step 304, dispersing one or more fibers in the mixture.
[0103] In other words, various embodiments may involve forming cement. Cement may include a binder comprising activated magnesium oxide cement. Cement may also include water. Cement may also include one or more fibers.
[0104] The binder component may further include any one or more binders selected from hydraulic cement, fly ash, silica fume and finely ground blast furnace slag.
[0105] In various embodiments, the mass percentage of active magnesium oxide cement in the binder component can be any percentage value selected from 40% to 100%.
[0106] In various embodiments, the mass ratio of water to binder components can be any ratio selected from 0.4 to 0.8.
[0107] In various embodiments, the mixture may further include a water-reducing agent, such as a sodium hexametaphosphate (Na(PO3)6) solution. The mass percentage of the water-reducing agent relative to the binder component may be any percentage value selected from 2% to 4%.
[0108] In various embodiments, the mixture may further include a viscosity control agent, such as hydroxypropyl methylcellulose. The mass percentage of the viscosity control agent relative to the binder component may be any percentage value selected from about 0.05% to about 0.5%.
[0109] In various embodiments, one or more fibers or polymer fibers may be any type of fiber selected from polyvinyl alcohol fibers, ethylene acetate fibers, polyethylene fibers, acrylic fibers, polypropylene fibers, and acrylamide fibers. The volume percentage of one or more fibers in the cementitious composition is any percentage value selected from 0.5% to 10%.
[0110] Each of one or more fibers may include an oil coating.
[0111] Various embodiments may involve a cementitious composition formed by any of the methods described herein.
[0112] Fiber-reinforced cementitious compositions can be prepared in any suitable manner. A method for preparing a fiber-reinforced cementitious composition may follow these steps: 1) mixing dry powders, including reactive MgO cement and supplementary binders such as fly ash; 2) mixing the above substances with water and a Na(PO3)6 solution for several minutes; 3) adding fibers (e.g., PVA fibers) to the fresh mixture and mixing until a homogeneous mixture is obtained. Cement-based structures can be formed by curing the composition under elevated CO2 conditions in ambient air or a manually controlled environment until it reaches the desired mechanical strength.
[0113] Various implementations may involve a method for forming a cement-based structure.
[0114] Figure 4 This is a schematic diagram illustrating a method for forming a cement-based structure according to various embodiments. The method may include, in step 402, forming a matrix comprising one or more hydrated magnesium carbonates. One or more fibers may be embedded in the matrix.
[0115] In other words, various embodiments may involve a method of forming a cement-based structure (e.g., concrete or mortar) comprising a matrix containing hydrated magnesium carbonate and various fibers within the matrix.
[0116] In various embodiments, the method may include embedding or dispersing one or more fibers in a matrix.
[0117] In various embodiments, forming the matrix may include forming a cementitious composition in which one or more fibers are embedded. The cementitious composition may include a mixture comprising a binder component (including activated magnesium oxide cement) and water. Forming the matrix may further include curing the cementitious composition by exposing it to carbon dioxide (CO2) to form one or more hydrated magnesium carbonates from the activated magnesium oxide cement.
[0118] In each embodiment, curing can be carried out for any suitable duration. In each embodiment, curing can be carried out for any suitable duration from 7 days to 28 days. Increasing the curing time may result in an increase in ultimate tensile strength and a decrease in strain hardening.
[0119] Curing can be carried out in a carbonization chamber or in air under ambient conditions. Curing can occur at any suitable temperature, such as any temperature selected from 25°C to 40°C, for example, at 30°C to 35°C. Curing can be carried out at any suitable CO2 concentration, such as any concentration selected from 5 vol% to about 20 vol%, for example, at about 10 vol%. Curing can be carried out at any suitable relative humidity, such as above 50%, for example above 60%, above 70%, above 80%, for example, about 90% relative humidity.
[0120] The formation of one or more hydrated magnesium carbonates can include the formation of brucite (Mg(OH)2) from activated magnesium oxide cement, and the formation of one or more hydrated magnesium carbonates from brucite. Magnesium oxide from activated magnesium oxide cement can react with water to form brucite. Brucite can react with carbon dioxide to form hydrated magnesium carbonates, such as magnesia (MgCO3·3H2O), hydromagnesite (4MgCO3·Mg(OH)2·4H2O), spheroidal magnesia (4MgCO3·Mg(OH)2·5H2O), and / or fibrous magnesite (MgCO3·Mg(OH)2·3H2O).
[0121] Various implementation methods may involve sequestering carbon dioxide from the atmosphere or the surrounding environment.
[0122] In various embodiments, one or more fibers may be bonded to the matrix.
[0123] In various embodiments, the cement-based structure can be concrete or mortar. Cement-based structures can achieve tensile ductility or tensile strain capacity of 1% or more. Various embodiments can have an average crack width of less than 150 μm, for example, less than 100 μm.
[0124] Experimental details
[0125] Experiment 1
[0126] Two exemplary mixtures are provided for the preparation of strain-hardening active MgO composites (SHMCs). These mixtures may include active MgO cement, fly ash, water, Na(PO3)6, and fibers. The mixing ratios are listed in Table 1. Active MgO cement supplied by International Scientific Ltd. of Singapore, fly ash supplied by Bisley Asia Pte Ltd. of Singapore, and Na(PO3)6 supplied by VMR Pte Ltd. of Singapore were used in both mixtures. Active MgO and fly ash were used as the main binders, while Na(PO3)6 was used as a water-reducing agent to achieve the desired processability for good fiber dispersion. Polyvinyl alcohol (PVA) fibers were manufactured by Kuraray Co. Ltd., Japan. The fiber length was 12 mm, and the fiber diameter was 39 μm. Two different fiber surface oil-coating contents, 0.0% and 1.2% relative to the fiber mass, were used in the two example mixtures (Mixture 1 and Mixture 2).
[0127]
[0128] Table 1 Exemplary mixing ratios
[0129] Compositions (mixture 1 and mixture 2) were prepared in a mixer with planetary rotating blades. The mixing process followed these steps: 1) dissolving Na(PO3)6 in water to form a Na(PO3)6 solution; 2) dry-mixing all the powdered solid raw materials, namely MgO cement and fly ash, for more than five minutes; 3) slowly adding the Na(PO3)6 solution to the dry powder mixture; 4) mixing the mixture for more than three minutes until the liquid and solids were uniformly mixed; 5) adding PVA fibers to the mixture; 6) continuing the mixing process for another three minutes. In mixture 1, the PVA fibers were not coated with an oil, while in mixture 2, the PVA fibers were coated with an oil.
[0130] The freshly prepared compositions (mixture 1 and mixture 2) were each cast into dog-bone shaped molds for uniaxial tensile testing. One day after preparation, the specimens were removed from the molds. The specimens were then cured for 7 days in a carbon dioxide (CO2) chamber (CO2 concentration = 10%, temperature = 35°C, relative humidity = 40%).
[0131] After curing, the powder was scraped off the sample. Two methods were used to quantify the amount of CO2 encapsulated during curing. First, the scraped powder was subjected to thermogravimetric analysis (TGA, 40℃–900℃, 10℃ / min) and differential thermal analysis (DTA, 40℃–900℃, 10℃ / min). Then, the scraped powder was decarburized using a 3N hydrochloric acid (HCl) solution, and the weight change due to CO2 release was measured. After 7 days of CO2 curing, uniaxial tensile tests were performed on the dog bone samples. The load-bearing capacity was set at 0.2 mm / min.
[0132] Figure 5A It is a graph showing the change of weight percentage (in percentage or %) / heat flow (in milliwatts or mW) with temperature (in degrees Celsius or °C), which shows the thermogravimetric analysis (TGA) and differential thermal analysis (DGA) results of the samples formed from mixture 1 and mixture 2 according to various embodiments.
[0133] For both hybrid designs, weight loss corresponding to the decomposition of hydrated magnesium carbonate (HMC) was observed between 388 °C and 900 °C (lines (i) and (ii)). Thermal absorption was also observed within the same temperature range (lines (iii) and (iv)). The amount of carbon dioxide (CO2) sequestered during curing could be quantitatively determined with respect to weight loss. Table 2 shows the CO2 sequestration measured by the TGA / DTA method and the hydrochloric acid (HCl) decarbonization method.
[0134]
[0135] Table 2 Density and CO2 sequestration of SHMC based on active MgO
[0136] Figure 5B It is a plot of tensile stress (expressed in megapascals or MPa) versus tensile strain (expressed as a percentage or %), which shows the uniaxial tensile stress-strain curve of the sample formed from mixture 1 according to various embodiments. Figure 5C This is a plot of tensile stress (expressed in megapascals or MPa) versus tensile strain (expressed as a percentage or %), showing the uniaxial tensile stress-strain curves of samples formed from mixture 2 according to various embodiments. It can be seen that both mixture 1 and mixture 2 achieve an ultra-high tensile ductility of at least 1%.
[0137] Commercial applications of compositions and structural / composite materials can include the manufacture of unreinforced structural and building components, including bricks, blocks and paving materials, with an estimated market size of US$8.9 billion (USD) in 2018.
[0138] Experiment 2
[0139] One of the key factors to consider when increasing the ductility of RMC-based strain-hardening composites (SHCs) is providing ideal fiber dispersion. Previous studies observing the rheology of fresh ECC mixtures have shown that high plastic viscosity and flowability, achievable by adjusting the water / binder (w / b) ratio and mixing design (e.g., fly ash (FA) content), can effectively prevent fiber entanglement, resulting in high ductility. Although increasing the w / b ratio reduces viscosity and leads to lower yield stress, the use of FA increases flowability and improves the rheological properties of cement mixtures due to the spherical shape of FA, which reduces interparticle friction. The relationship between the rheology and tensile ductility of cement paste, evaluated by measuring the uniformity of fiber dispersion, has revealed that the increase in viscosity due to good fiber dispersion can enable even higher ductility.
[0140] While ideal fiber dispersion is crucial, it does not necessarily guarantee strain hardening behavior or high ductility. Figure 6 This is a plot of the fiber bridging stress (σ) versus crack opening displacement (δ). The plot shows the tensile stress-crack opening displacement curve and strain hardening criteria, illustrating the constitutive law of fiber bridging. (For example...) Figure 6 As shown, the hardened composite material may need to meet two strain hardening criteria. Specifically, as shown in equation (1), the residual energy J of the fiber bridging curve may be required. b’ (i.e., the shaded area) has a crack tip toughness J greater than that of the matrix. tip .
[0141] (1)
[0142] It is the maximum fiber bridging strength, and This corresponds to the maximum fiber bridging strength. The cracks opened. Additionally, It is the steady-state crack strength, while It corresponds to the steady-state crack strength The cracks opened.
[0143] Furthermore, as shown in equation (2), the maximum fiber bridging strength may be required. (i.e., the peak of the curve) is higher than the tensile strength of the matrix. .
[0144] (2)
[0145] Since fiber bridging and matrix crack tip toughness are influenced by factors such as the w / b ratio, fiber aspect ratio, and the bond between the fiber and the cement matrix (which may be affected by fiber surface treatment), it may be important to study the effects of these factors on the tensile properties of RMC-based strain hardening composites (SHCs).
[0146] Various embodiments may involve strain-hardening composite materials (SHCs) or structures based on RMC. During the formation of the composite material or structure, the various embodiments associated with each composite material or structure may be affected by key parameters.
[0147] The first part of Experiment 2 focused on the effects of the water / binder (w / b) ratio and fly ash (FA) content on the rheological properties of the RMC composition or paste, aiming to determine a suitable blending design that results in the desired viscosity and sufficient flowability to achieve good fiber dispersion. The second part of Experiment 2 focused on the inclusion of fibers in the blending design determined in the first phase and investigated the effects of certain factors (e.g., w / b ratio, fiber aspect ratio, fiber surface treatment, and curing age) on the developed formulation.
[0148] Material
[0149] Reactive magnesium oxide cement (RMC) obtained from International Science Ltd. (Singapore) was the primary binder used in this study. Grade F fly ash (FA) obtained from Bisley Asia Ltd. (Malaysia) was used to adjust the rheology of the fresh mixture and was used as a binder via the pozzolanic reaction of fly ash with brucite.
[0150] Table 3 shows the chemical composition of active magnesium oxide cement (RMC) and fly ash (FA).
[0151]
[0152] Table 3 Chemical composition of RMC and FA
[0153] Figure 7 This is a graph showing the cumulative fraction (expressed as a percentage or %) as a function of particle diameter (expressed in micrometers or μm), illustrating the particle size distribution of the active magnesium oxide cement (RMC) and fly ash (FA) used in the compositions according to various embodiments.
[0154] Sodium hexametaphosphate (Na(PO3)6), obtained from VWR International Ltd. (Singapore), was added as a water-reducing agent at 10% of the water content to the prepared formulation. Polyvinyl alcohol (PVA) fiber, one of the most commonly used fiber types in ECC, was obtained from Kuraray Ltd. (Japan) and included in the selected RMC-SHC samples in three different forms with different aspect ratios (i.e., 8 mm and 12 mm lengths) and surface treatments (i.e., oil coating (OC) and no oil-coating (NC)). Table 4 lists the properties of the PVA fibers used in this study.
[0155]
[0156] Table 4. Performance of the PVA fibers used in this study.
[0157] method
[0158] As emphasized above, the first part of Experiment 2 investigated the effects of the water / binder (w / b) ratio and fly ash / binder (FA / b) ratio on the rheology of the fresh mixture before fiber encapsulation. The aim of this part was to determine the appropriate blending design (i.e., w / b ratio and FA content) that leads to the desired plastic viscosity and flowability for good fiber dispersion. In the second part, which incorporates PVA fibers into the blending design determined in the first part, the effects of w / b ratio, fiber aspect ratio, fiber surface treatment (i.e., oil content), and curing age on the mechanical properties of the RMC-based strain-hardening composite (SHC) were investigated.
[0159] Table 5 provides detailed information on the seven different mixing ratios prepared in the first part of the study.
[0160]
[0161] Table 5 shows the mixing ratios of the fiber-free RMC mixtures prepared for rheological measurements.
[0162] The sample names were denoted in the format FA(X)-(Y), where X represents the FA content (i.e., the percentage of total binder) and Y represents the w / b ratio. A range of w / b (0.47–0.58) and FA / b (0–0.6) ratios were determined from the preliminary samples prepared for each formulation.
[0163] The sample preparation process begins with dissolving Na(PO3)6 in a predetermined amount of water. This solution is then added to a dry mixture of RMC and FA during mixing. A stopwatch is set to sound two minutes after the moment the solution is added to the dry RMC-FA mixture. After two minutes of mixing, a spoonful of the fresh mixture is placed on a 39 mm diffusion base plate on the rheometer, fitted with a 39 mm P35 TiL top plate, which is pressed against the mixture at 0.5 N.
[0164] Rheological measurements were performed using a HAAKE MARS III 379-0400 rheometer, which is used to measure the shear resistance of fresh mixtures at specified rotational speeds. Figure 8A A rheometer for measuring samples according to various embodiments is shown. Figure 8B Test setups for measuring samples according to various embodiments are shown.
[0165] Three rheological measurements were performed at 6, 12, and 18 minutes. For each measurement, the top plate was first rotated at a relatively high speed (approximately 50 / s) for 30 seconds to prevent any agglomeration, followed by an increase in the shear rate from 1 / s to 100 / s over 180 seconds. The shear resistance τ was recorded for a total of 210 seconds. The sample was held in place between measurements. Sample preparation and subsequent measurements were performed at ambient temperature (25°C).
[0166] A certain level of plastic viscosity is crucial for good fiber dispersion and tensile ductility. The results of the first part of the study were used to select the w / b and FA / b ratios to be incorporated in the mixing design in the second part. Previous literature has shown that although the fiber dispersion coefficient increases with plastic viscosity, tensile ductility stabilizes after reaching a threshold fiber dispersion coefficient. This value corresponds to a plasticity of approximately 3.5 Pa∙s, and this value was also used in this study to prepare the samples used in the tensile property tests. Referring to the results obtained in the first part of the study to identify samples exhibiting good fiber dispersion (e.g., FA30-0.53), the four mixing ratios listed in Table 6 were prepared to evaluate the effects of w / b ratio, fiber aspect ratio, fiber surface treatment (i.e., oil content), and curing age on the tensile performance of RMC-based strain-hardening composites (SHCs).
[0167]
[0168] Table 6 shows the mixing ratios prepared for testing hardened tensile properties.
[0169] Sample names were notated in the format (X)-(Y)-(Z), where X, Y, and Z represent fiber surface treatment, fiber length, and w / b ratio, respectively. The term "OC" for (X) refers to oil coating, while "NC" refers to oil-free coating. Units for (Y) are in millimeters (mm). For all hybrid designs, based on rheological measurements, the FA / b ratio was kept constant at 0.3, while the w / b ratio remained ≤0.53. Consistent with previous literature on ECC, a constant fiber fraction corresponding to 2% binder content was used.
[0170] To begin sample preparation, RMC and FA were dry-mixed in a planetary mixer for more than 3 minutes, then the prepared Na(PO3)6 solution was slowly added to form a fresh mixture. The mixing process continued for another 2 to 3 minutes until a homogeneous mixture was obtained, and then PVA fibers were slowly added over 2 minutes. Throughout the mixing process, the blade rotation speed was kept constant at 6.4 rad / s.
[0171] The prepared mixture was cast into a cubic (50×50×50mm) dog bone-shaped mold, the external dimensions of which are shown in the figure. Figure 9A middle. Figure 9A Top and side views of a dog bone-shaped mold according to various embodiments are shown.
[0172] The cast samples were stored in a sealed container dehumidified using silica gel. After 3 days, the samples were removed from their molds and cured for 7 days in a carbonization chamber set at 10% CO2 concentration, 30°C, and 90% relative humidity (RH). The effect of curing duration was investigated by exposing one sample (NC-12-0.41) prepared under the same conditions to carbonization curing for a total of 28 days.
[0173] Once curing is complete, the compressive strength of the cubic specimens is measured. Three specimens for each cubic specimen are measured according to the ASTM C109 / C109M-13 specification. The equipment used for the compression test is a Landmark 370.25, operated at a loading rate of 0.25 mm / min. Figure 9B As shown, uniaxial tensile tests were performed on at least three specimens of each hybrid design using an Instron 5569. Figure 9B Test setups for uniaxial tensile testing of samples are shown according to various embodiments.
[0174] During the testing, the loading rate was set to 0.02 mm / min, and two linear variable differential ransformers (LVDTs) were used to determine the gauge length extension (approximately 60 mm to approximately 70 mm). Following uniaxial tensile testing, the crack width and spacing of each specimen were determined using a Nikon DS-Fi2 high-resolution camera at approximately 420x magnification. For each hybrid design, 3 to 6 specimens were analyzed to evaluate their crack patterns.
[0175] In addition to compressive and tensile strength, CO2 uptake of selected samples during carbonization and curing was assessed by obtaining representative powder from each sample. These powders were milled to pass through a 75 μm sieve and vacuum dried prior to analysis. Quantitative measurements were performed by thermogravimetric analysis / differential scanning calorimetry (TGA / DSC) on a Perkin Elmer TGA 4000 instrument. During TGA / DSC, samples were heated from approximately 40 °C to approximately 900 °C at a heating rate of approximately 10 °C / min under a nitrogen flow.
[0176] discuss
[0177] Rheological properties
[0178] Figure 10A This is a plot of torque τ (in Pascals or Pa) versus shear rate N (per second or 1 / s), showing the torque shear rate (τ-N) of sample FA60-0.53 according to various embodiments at 6 minutes, 12 minutes, and 18 minutes. Figure 10B This is a plot of torque τ (in Pascals or Pa) versus shear rate N (per second or 1 / s), showing the torque shear rate (τ-N) of sample FA60-0.53 according to various embodiments at 6 minutes, 12 minutes, and 18 minutes.
[0179] Figure 10A-B can be used to show the relationship between the shear resistance τ (Pa) and the shear rate N ( / s) of a fresh RMC mixture at different elapsed times. The curve shows that the fresh mixture (i.e., fiber-free) is a Bingham liquid, where the shear force exceeds the initial mixture resistance and rotation begins. Thereafter, the shear resistance increases linearly with rotational speed N ( / s), showing no shear thinning or shear thickening effect. The fresh mixture is fiber-free. Equation 3 quantitatively describes the relationship between τ and N for the Bingham liquid, where g (Pa) (the y-intercept) is the yield stress required to break the interaction network between particles and initiate rotation; h (Pa·s) (the slope of the curve) is the plastic viscosity.
[0180] (3)
[0181] For any given fresh mixture at a specified time, g and h are constants representing the rheological properties of the mixture.
[0182] In conventional cement-based fresh mixtures, the shear rate (N) and solid volume fraction (V) change with increasing shear rate (N) and solid volume fraction (V). s The varying shear resistance depends on several types of particle interactions (i.e., van der Waals forces, direct contact forces between particles, and hydrodynamic forces, due to which friction between fluid layers increases with velocity). At relatively low shear rates, the yield stress (g) can be determined primarily by van der Waals forces or direct contact forces. Previous studies on the yield stress of C3S pastes with similar particle sizes to RMC have shown that the critical V... s At a value of 0.38, above which the solid particles become so compact that the dominant particle interactions shift from van der Waals forces to direct contact forces. This is in addition to FA0-0.58 (V s =0.35) and FA30-0.58 (V s Apart from V = 0.37), most of the hybrid designs that appeared in this study... s A value greater than 0.38 indicates that direct contact forces dominate. At relatively high shear rates, although van der Waals forces and direct contact forces still exist, the yield stress is primarily determined by hydrodynamics.
[0183] Table 7 provides the measured values of yield stress (g) and plastic viscosity (h) for all samples at different elapsed times.
[0184]
[0185] Table 7 Rheological test results
[0186] For some mixtures, the shear resistance was underestimated due to loss of contact between the top plate and the fresh mixture, therefore the g and h values at 12 and 18 minutes are not listed. The “-” in Table 7 indicates that g and h were not listed due to loss of contact between the top plate and the fresh mixture. The symbol for the sample name follows the format FA(X)-(Y), where X represents the FA content (i.e., the percentage of total binder) and Y represents the w / b ratio.
[0187] It can be observed that g and h generally increase over time. This may be related to the precipitation of brucite (Mg(OH)2) on the surface of RMC particles, which increases the direct contact between particles by increasing the solid particle size, thus resulting in additional resistance between fluid layers.
[0188] Figure 11A -B shows the effect of water and FA content on the rheological properties of the RMC sample, where it is observed that the yield stress (g) and plastic viscosity (h) tend to decrease with increasing water content. Figure 11A A plot showing the plastic viscosity (in Pascals seconds or Pas) as a function of the fly ash / binder ratio (FA / b) (in percentage or %) is presented, illustrating the effect of water and fly ash content on the plastic viscosity of the mixture according to various embodiments. Figure 11B A plot showing the yield stress (in Pascals or Pa) as a function of the fly ash / binder ratio (FA / b) (in percentage or %) is presented, illustrating the effect of water and fly ash content on the yield stress of the mixture according to various embodiments.
[0189] The decrease in plastic viscosity and yield stress with increasing w / b ratio can likely be attributed to the higher liquid content, which reduces direct contact between particles. While increasing FA content from 0% to 30% leads to an increase in plastic viscosity, it may not have a profound effect on yield stress because particle shape has a limited influence on V. s The effect is not significant at <0.38, and its influence on direct contact force may be limited.
[0190] The increase in plastic viscosity with increasing FA content is likely due to the enhancement of van der Waals forces, which is caused by the increase in V... s With the increase of FA content, the distance between particles decreased. The relatively constant yield stress of samples FA0-0.58 and FA30-0.58 is likely due to the loose compaction of particles within these two mixtures, thus limiting the effect of particle shape on van der Waals forces. Further increasing the FA content from 30% to 60% resulted in a decrease in both g and h at all w / b ratios.
[0191] Although FA has a lower density than RMC (2400 kg / m³), 3 With 3230kg / m3 It can be expected that the solid volume fraction will increase with increasing FA content, but the yield stress and plastic viscosity will decrease with increasing FA content, which may be attributed to the spherical geometry of FA particles, which reduces the contact force between particles.
[0192] Mechanical properties
[0193] Based on the above rheological results, samples containing 30% FA (i.e., FA / b = 0.3) with a w / b ratio ≤ 0.53 were prepared for further analysis. The w / b ratio was reduced to obtain higher viscosity, thus achieving better fiber dispersion. Consistent with previous literature on ECC, fibers were introduced into these mixtures at a fixed amount of 2% of the RMC-SHC paste volume.
[0194] The effects of key factors (such as fiber surface treatment (oil-coated (OC) vs. uncoated (NC)), fiber aspect ratio (8 mm vs. 12 mm length), w / b ratio (0.41 vs. 0.53), and curing duration (7 days vs. 28 days)) on the compressive and tensile strength of carbonized RMC-based samples were investigated.
[0195] The mechanical properties of the samples are presented in Table 8. As emphasized above, the symbols for the sample names follow the format (X)-(Y)-(Z), where X, Y, and Z represent fiber surface treatment, fiber length, and w / b ratio, respectively. The term "OC" used for (X) refers to oil coating, while the term "NC" refers to oil-free coating. The units for (Y) are expressed in millimeters (mm).
[0196]
[0197] Table 8. Mechanical test results.
[0198] Crack spacing can be calculated as follows:
[0199] Crack spacing (mm) = gauge length / number of cracks (4)
[0200] The tensile stress recorded at the onset of the first crack is called the "initial crack strength," while the tensile stress and tensile strain near specimen failure are called the "ultimate tensile strength" and "tensile strain capacity," respectively. In addition to the initial crack strength, ultimate tensile strength, and tensile strain capacity, Table 8 also lists the crack spacing and average crack width for each sample. For most samples, the overall high tensile strain capacity exceeding 1%, coupled with crack widths limited to less than 100 μm, likely indicates strain-hardening behavior and tensile ductility in the RMC-based composite material.
[0201] Figure 12A-E illustrates the relationship between tensile stress and tensile strain for composite materials formed from each mixture. As emphasized above, the notation for sample names follows the format (X)-(Y)-(Z), where X, Y, and Z represent fiber surface treatment, fiber length, and w / b ratio, respectively. The term "OC" for (X) refers to oil coating, while the term "NC" refers to oil-free coating. Units for (Y) are expressed in millimeters (mm).
[0202] Figure 12A This is a plot of tensile stress (expressed in megapascals or MPa) versus tensile strain (expressed as a percentage or %), illustrating the tensile stress-strain curves of sample NC-12-0.41 after 7 days of curing according to various embodiments. Figure 12B It is a plot of tensile stress (expressed in megapascals or MPa) versus tensile strain (expressed as a percentage or %), illustrating the tensile stress-strain curves of sample NC-12-0.41 after curing for 28 days according to various embodiments. Figure 12C This is a plot of tensile stress (expressed in megapascals or MPa) versus tensile strain (expressed as a percentage or %), illustrating the tensile stress-strain curves of sample OC-12-0.41 after 7 days of curing according to various embodiments. Figure 12D It is a plot of tensile stress (expressed in megapascals or MPa) versus tensile strain (expressed as a percentage or %), illustrating the tensile stress-strain curves of sample OC-12-0.53 after 7 days of curing according to various embodiments. Figure 12E It is a plot of tensile stress (expressed in megapascals or MPa) versus tensile strain (expressed as a percentage or %), illustrating the tensile stress-strain curves of sample OC-8-0.53 after 7 days of curing according to various embodiments.
[0203] Different elastic and strain-hardening stages were observed within each sample. In the elastic stage, tensile stress may develop linearly with strain. The increasing load leads to the introduction of initial cracks, which may mark the beginning of the strain-hardening stage. During the strain-hardening stage, tensile stress increases slowly with strain, accompanied by the gradual formation of multiple fine cracks that can characterize ductility. Near the end of strain hardening, tensile stress may begin to decrease sharply due to the deterioration of fiber bridging followed by localized damage with increasing load. At this point, due to the spring effect of the fiber bridging, the load is immediately released after specimen failure, leading to the shrinkage of most of the cracks.
[0204] Figure 13 The image shows a typical crack distribution of a destructive specimen (NC-12-0.41 cured for 7 days) after unloading according to various embodiments. Figure 13 Multiple cracks were observed in the RMC-based sample. Figure 14A A typical fracture surface can be seen, which reveals the fiber layout at the location of the crack at the point of failure. Figure 14A It illustrates various embodiments. Figure 13 The image shown is of the fracture surface of the specimen. The fracture surface has several pulled-out fibers.
[0205] exist Figure 14B and 14C The image shows the fibers pulled out at the break point and the remaining fiber tunnels, respectively. Figure 14B It is based on the various implementation methods Figure 14A The image shown is a field emission scanning electron microscope (FESEM) image of the pulled-out fiber. Figure 14C It is based on the various implementation methods. Figure 14B The image shown is a field emission scanning electron microscope (FESEM) image of the residual tunnels in the matrix after the fibers were pulled out.
[0206] These images show that the fiber surface is smooth with very little matrix debris adhering to it, indicating that most of the fibers were pulled out rather than broken. This suggests that the fiber strength may not be fully utilized in the developed formulation, and the limiting factor may be the fiber-matrix interface, which could be further enhanced.
[0207] The effect of fiber surface treatment (samples OC-12-0.41 and NC-12-0.41)
[0208] The effect of fiber surface treatment on sample performance can be assessed by comparing samples with oil-coated fibers (OC-12-0.41) and samples with uncoated fibers (NC-12-0.41) to evaluate the impact of the presence of oil coating on sample performance. Both types of samples can be cured for 7 days before testing.
[0209] Although there was no significant difference in compressive strength between the two samples, the presence of oil coating greatly increased tensile ductility from 2.64% to 3.26% (approximately 47 μm for NC-12-0.41 and approximately 84 μm for OC-12-0.41), due to the larger crack width observed with the use of oil-coated fibers.
[0210] The presence of an oil coating on the fiber can reduce fiber-matrix interfacial bonding, resulting in a wider crack spacing with a larger crack width. Therefore, although at the cost of increased crack width, adjusting the oil content applied to the fiber surface may be an effective means of improving the ductility of RMC-SHC, which may lead to increased water permeability and reduced long-term durability.
[0211] Effect of fiber aspect ratio (samples OC-8-0.53 and OC-12-0.53)
[0212] The effect of fiber length difference on fiber aspect ratio can be assessed by comparing sample OC-8-0.53 with a fiber wrapping length of 8 mm and sample OC-12-0.53 with a fiber wrapping length of 12 mm. An increase in fiber aspect ratio may lead to a significant improvement in tensile strength and ductility.
[0213] From the study of the destruction mechanism of the sample, we can see that... Figure 14A The study shows that most of the fibers within the matrix are stretched rather than broken. This reveals the potential for weak bonding between the fibers and the matrix within the composite material. Figure 14A The samples in the study did not fully utilize the fiber strength during the pull-out process. Increasing the fiber embedding length may result in greater resistance to pull-out forces, leading to better fiber bridging and stronger strain hardening.
[0214] Effect of w / b ratio (samples OC-12-0.41 and OC-12-0.53)
[0215] The effect of w / b on the compressive and tensile strength of the RMC-SHC formulation can be determined by comparing samples OC-12-0.41 and OC-12-0.53. A decrease in compressive strength was observed as the w / b ratio increased from 0.41 to 0.53. This may be related to the reduced diffusion rate of carbon dioxide (CO2) within the saturated porous system at higher water content, which reduces the degree of carbonation and the formation of the associated strength of the carbonate phase; and the increased porosity due to the presence of additional free water. Besides weakening the matrix, the fiber-matrix interface may also be weakened, leading to a decrease in the bonding strength between the fiber and the matrix. On the other hand, decreasing the w / b ratio from 0.53 to 0.41 not only enhanced the initial crack strength and ultimate tensile strength but also provided better tensile ductility. The reduced crack spacing and average crack width further revealed the strain hardening effect and improved fiber bridging.
[0216] The effect of curing time (sample NC-12-0.41 at 7 days vs. 28 days) )
[0217] The effect of curing duration on sample properties was determined by studying one sample of NC-12-0.41 cured for 7 days and another sample of NC-12-0.41 cured for 28 days. Strength results showed that the ultimate tensile strength likely improved with increasing curing duration, while tensile ductility remained almost unchanged. The enhanced ultimate strength may be related to improved fiber bridging, possibly attributed to the continued formation of the carbonate phase, which strengthened the fiber-matrix interface during the 28-day curing period. Increases in crack spacing and average crack width were observed as the curing duration increased from 7 days to 28 days, indicating reduced strain hardening, which is influenced by the improved matrix toughness at longer curing durations.
[0218] Carbon dioxide (CO2) sequestration
[0219] The amount of CO2 sealed during the curing process was quantified using thermogravimetric analysis (TGA) / differential scanning calorimetry (DSC). Figure 15 It is a plot of mass (expressed as a percentage or %) / heat flow (expressed as milliwatts or mW) as a function of temperature (expressed as degrees Celsius or °C), which shows the thermogravimetric analysis (TGA) curves and differential scanning calorimetry (DSC) curves of sample OC-12-0.53 according to various embodiments.
[0220] The mass loss below 100°C is due to the loss of hygroscopic water, followed by two distinct endothermic peaks. The first peak at approximately 320°C likely corresponds to the removal of water of crystallization from the Mg carbonate formed during carbonation and curing, and the decomposition of uncarbonized hydrates (Mg(OH)₂) into MgO. The second peak at approximately 460°C likely corresponds to the decarbonation of the carbonate phase, leaving MgO at the end of the analysis. Quantification of the mass loss above 460°C associated with CO₂ loss from the carbonized RMC system indicates an average degree of carbonation of approximately 10%. These results suggest that sequestering CO₂ in the form of stable carbonates within the prepared formulation not only provides a safe storage of atmospheric CO₂ but also facilitates the development of a class of strain-hardening composites that do not require the use of any Portland cement (PC).
[0221] Although the invention has been specifically shown and described with reference to specific embodiments, those skilled in the art will understand that various changes in form and detail may be made without departing from the spirit and scope of the invention as defined by the appended claims. Therefore, the scope of the invention is indicated by the appended claims, and thus is intended to cover all changes falling within the meaning and scope of equivalents of the claims.
Claims
1. A cementitious composition comprising: The mixture comprises: The binder component includes activated magnesium oxide cement; and Water; and One or more fibers, wherein the one or more fibers are dispersed in the mixture.
2. The cementitious composition according to claim 1, characterized in that, The binder component also includes any one or more binders selected from hydraulic cement, fly ash, silica fume and finely ground blast furnace slag.
3. The cementitious composition according to claim 1 or claim 2, characterized in that, The mass percentage of the active magnesium oxide cement in the binder component is selected from any percentage value between 40% and 100%.
4. The cementitious composition according to any one of claims 1 to 3, characterized in that, The mass ratio of water to the binder component is selected from any ratio between 0.4 and 0.
8.
5. The cementitious composition according to any one of claims 1 to 4, characterized in that, The mixture also includes a water-reducing agent.
6. The cementitious composition according to claim 5, characterized in that, The water-reducing agent is a sodium hexametaphosphate solution.
7. The cementitious composition according to claim 5 or claim 6, characterized in that, The water-reducing agent is selected from any percentage value between 2% and 4% by mass relative to the binder component.
8. The cementitious composition according to any one of claims 1 to 7, characterized in that, The mixture also includes a viscosity control agent.
9. The cementitious composition according to claim 8, characterized in that, The viscosity control agent is hydroxypropyl methylcellulose.
10. The cementitious composition according to claim 8 or claim 9, characterized in that, The viscosity control agent is selected from any percentage value between 0.05% and 0.5% by mass relative to the binder component.
11. The cementitious composition according to any one of claims 1 to 10, characterized in that, The one or more fibers are any type of fiber selected from metal fibers, polymer fibers, and natural fibers.
12. The cementitious composition according to any one of claims 1 to 11, characterized in that, The volume percentage of the one or more fibers in the cementitious composition is selected from any percentage value from 0.5% to 10%.
13. The cementitious composition according to any one of claims 1 to 12, characterized in that, Each of the one or more fibers includes an oil coating.
14. A cement-based structure, comprising: The matrix comprises one or more hydrated magnesium carbonates; and One or more fibers, which are embedded in the matrix.
15. The structure according to claim 14, characterized in that, The one or more hydrated magnesium carbonates are selected from magnesia, hydromagnesite, spheroidal magnesia, and fibrous magnesite.
16. The structure according to claim 14 or claim 15, characterized in that, One or more fibers are bonded to the matrix.
17. The structure according to any one of claims 14 to 16, characterized in that, The cement-based structure is concrete.
18. A method for forming a cementitious composition, the method comprising: A mixture is formed, the mixture comprising: The binder component includes activated magnesium oxide cement; and Water; and One or more fibers are dispersed in the mixture.
19. The method according to claim 18, characterized in that, The binder component also includes any one or more binders selected from hydraulic cement, fly ash, silica fume and finely ground blast furnace slag.
20. The method according to claim 18 or claim 19, characterized in that, The mass percentage of the active magnesium oxide cement in the binder component is selected from any percentage value between 40% and 100%.
21. The method according to any one of claims 18 to 20, characterized in that, The mass ratio of water to the binder component is selected from any ratio between 0.4 and 0.
8.
22. The method according to any one of claims 18 to 21, characterized in that, The mixture also includes a water-reducing agent.
23. The method according to claim 22, characterized in that, The water-reducing agent is a sodium hexametaphosphate solution.
24. The method according to claim 22 or claim 23, characterized in that, The water-reducing agent is selected from any percentage value between 2% and 4% by mass relative to the binder component.
25. The method according to any one of claims 18 to 24, characterized in that, The mixture also includes a viscosity control agent.
26. The method according to claim 25, characterized in that, The viscosity control agent is hydroxypropyl methylcellulose.
27. The method according to claim 25 or claim 26, characterized in that, The viscosity control agent is selected from any percentage value between 0.05% and 0.5% by mass relative to the binder component.
28. The method according to any one of claims 18 to 27, characterized in that, The one or more fibers are any type of fiber selected from metal fibers, polymer fibers, and natural fibers.
29. The method according to any one of claims 18 to 28, characterized in that, The volume percentage of the one or more fibers in the cementitious composition is selected from any percentage value from 0.5% to 10%.
30. The method according to any one of claims 18 to 29, characterized in that, Each of the one or more fibers includes an oil coating.
31. A method for forming a cement-based structure, the method comprising: A matrix is formed, the matrix comprising one or more hydrated magnesium carbonates; One or more fibers are embedded in the matrix.
32. The method according to claim 31, characterized in that, Forming the matrix, wherein one or more fibers are embedded in the matrix, comprising: A cementitious composition is formed, the cementitious composition comprising: The mixture comprises: The binder component includes activated magnesium oxide cement; and Water; and One or more fibers, said one or more fibers dispersed in the mixture; and The cementitious composition is cured by exposing it to carbon dioxide. The active magnesium oxide cement is used to form one or more hydrated magnesium carbonates.
33. The method according to claim 32, characterized in that, The formation of one or more hydrated magnesium carbonates includes: The active magnesium oxide cement forms brucite; and One or more hydrated magnesium carbonates are formed from the brucite.
34. The method according to any one of claims 31 to 33, characterized in that, The one or more hydrated magnesium carbonates are selected from magnesia, hydromagnesite, spheroidal magnesia, and fibrous magnesite.
35. The method according to any one of claims 31 to 34, characterized in that, One or more fibers are bonded to the matrix.
36. The method according to any one of claims 31 to 35, characterized in that, The cement-based structure is concrete.